Neutrophil Extracellular Trap Targeting Protects Against Ischemic Damage After Fibrin-Rich Thrombotic Stroke Despite Non-Reperfusion - Peña-Martínez, Carolina; Durán-Laforet, Violeta; García-Culebras, Alicia; Cuartero, María Isabel; Moro, María Ángeles; Lizasoain, Ignacio (Frontiers in Immunology, 2022)
Stroke is one of the most prevalent diseases worldwide caused primarily by a thrombotic vascular occlusion that leads to cell death. To date, t-PA (tissue-type plasminogen activator) is the only thrombolytic therapy approved which targets fibrin as the main component of ischemic stroke thrombi. However, due to its highly restrictive criteria, t-PA is only administrated to less than 10% of all stroke patients. Furthermore, the research in neuroprotective agents has been extensive with no translational results from medical research to clinical practice up to now. Since we first described the key role of NETs (Neutrophil Extracellular Traps) in platelet-rich thrombosis, we asked, first, whether NETs participate in fibrin-rich thrombosis and, second, if NETs modulation could prevent neurological damage after stroke. To this goal, we have used the thromboembolic in situ stroke model which produces fibrin-rich thrombotic occlusion, and the permanent occlusion of the middle cerebral artery by ligature. Our results demonstrate that NETs do not have a predominant role in fibrin-rich thrombosis and, therefore, DNase-I lacks lytic effects on fibrin-rich thrombosis. Importantly, we have also found that NETs exert a deleterious effect in the acute phase of stroke in a platelet-TLR4 dependent manner and, subsequently, that its pharmacological modulation has a neuroprotective effect. Therefore, our data strongly support that the pharmacological modulation of NETs in the acute phase of stroke, could be a promising strategy to repair the brain damage in ischemic disease, independently of the type of thrombosis involved.